Prevention of neural tube defects in an urban health district. Issue 3 (September 1983) - Watson, D; Pow, M; Ellam, A; Costeloe, K
Abstract : An evaluation of voluntary prenatal screening for neural tube defects with serum alphafetoprotein (s-AFP) is presented. During a three year period, there were 52 fetuses with neural lesions. Of 46 mothers who bore a fetus with an open neural lesion, 25 were detected, of whom 23 agreed to the termination of their pregnancies. An unscreened group of 2331 mothers (17% of all deliveries) produced 14 fetuses with neural tube defects, an incidence of 6.0 per 1000, 1.8 times the incidence (3.3 per 1000) in the screened group. Pitfalls occurring in the assessment of hyper-alphafetoproteinemia included inaccurate gestational dating and allowance for excessive body weight. The results of a robust AFP-NTD screening programme supported in selected cases by ultrasonar visualisation of the spine argue for its continuance in this district.